Helper T cells (CD3+/CD4+) within the autologous peripheral blood stem cell graft positively correlate with event free survival of multiple myeloma patients - Schmidmaier, R.; Oversohl, N.; Schnabel, B.; Straka, C.; Emmerich, B. (Experimental Oncology, 2008)
The microenvironment in the bone marrow — including lymphocytes — is part of the pathophysiology of multiple myeloma (MM). High dose chemotherapy followed by autologous stem cell transplantation is standard of care for younger patients. Aim: To determine the influence of reinfused lymphocyte subsets on event free survival (EFS) and overall survival (OS). Methods: In peripheral blood (PB) and aphaeresis products (AP) of 41 MM patients lymphocyte subsets were determined by flow cytometry and were correlated with clinical outcome. Results: PB lymphocyte subsets did not influence EFS or OS. Residual plasma cells in the AP were not correlated with poor outcome, whereas a high percentage of B cells (CD19+) showed a trend towards reduced EFS (P = 0.051). A high amount of CD4 cells and an increased CD4/CD8 ratio were significantly associated with prolonged EFS. In contrast, high percentage of HLA-DR positive lymphocytes showed negative impact on EFS and OS (P = 0.03 and 0.02, respectively). Conclusion: Obtained data suggest the non-activated (HLA-DR negative) helper CD4+ T cells in the AP to be tumour protective. Микроокружение в костном мозге, включая лимфоциты, оказывает влияние на патофизиологию множественной миеломы
(MM). Высокодозовая химиотерапия, за которой следует аутологическая трансплантация стволовых клеток, является
стандартным подходом при лечении более молодых пациентов. Цель: изучить влияние введенных субпопуляций лимфоцитов
на безрецидивную выживаемость (EFS) и общую выживаемость больных c ММ. Методы: методом проточной цитофлуориметрии
в периферической крови (PB) и продуктах афереза (АР) пациентов с ММ ( n = 41) изучали субпопуляции
лимфоцитов и возможную корреляцию с исходом болезни. Результаты: субпопуляции лимфоцитов РB не влияли на EFS
или OS. Остаточные клетки плазмы в АР не коррелировали с плохим прогнозом, в тоже время при высоком содержании
В-клеток (CD19+) отмечали тенденцию к снижению EFS (P = 0,051). Высокое содержание CD4-клеток и увеличение
соотношения CD4/CD8 были достоверно ассоциированы с повышением EFS. В отличие от этого, высокий процент HLADR-положительных
лимфоцитов имел отрицательное влияние на EFS и OS (P = 0,03 и 0,02 соответственно). Выводы:
полученные данные позволяют предположить, что неактивированные (HLA-DR-отрицательные) хелперные CD4+ T-клетки
в AP могут обладать антиопухолевыми свойствами.